Evaluasi Kualitas Udara dalam Ruang: Studi Deskriptif Paparan PM2,5 pada Toko Bangunan - Deddy Alif Utama; Syakila Gita Diandra; Yazmin Armin Abdullah (Poltekkes Kemenkes Semarang, 2025)
Activities in building material stores potentially pollute indoor air through construction dust, particularly PM2.5, which poses significant health risks. This study aimed to evaluate indoor air quality regarding PM2.5 concentrations and identify respiratory complaints among workers at Building Material Store X, Gorontalo City. This descriptive observational study involved 15 active workers (total sampling) and measured PM2.5 concentrations at three strategic working points using a Portable Dust Monitor for one hour at five-minute intervals. The results indicated that all sampling points exceeded the threshold value of the Indonesian Ministry of Health Regulation Number 2 of 2023 (25 μg/m3), falling into the category of Not Meeting Requirements. The highest extreme concentration was found in the Cement Warehouse at 1,244.95 μg/m3 (nearly 50 times the threshold value), while the lowest concentration in the showcase area was recorded at 52.77 μg/m3. The health profile of workers revealed a dominance of upper respiratory tract irritation symptoms, with 60% of workers experiencing sneezing, 13.3% coughing, and 6.7% reporting chest tightness. The high particulate exposure, resulting from poor ventilation and lack of personal protective equipment compliance, classifies this work environment as hazardous, necessitating technical ventilation interventions and strict enforcement of occupational health and safety regulations.